2016
DOI: 10.1021/acs.jpcb.6b00228
|View full text |Cite
|
Sign up to set email alerts
|

Direct Phase Equilibrium Simulations of NIPAM Oligomers in Water

Abstract: 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 45 publications
5
65
0
Order By: Relevance
“…It is known that the chain length and concentration of the polymer can affect the process of LCST phase transition. For example, to observe a clear conformational transition in the case of computational studies of PNIPAAm, it was found that either the polymer chain length should be at least 30‐mer or the oligomer concentration should be high . In our single chain simulations, we observed a similar behavior for PMEO 2 MA that only 20‐ and 50‐mer polymers showed a LCST phase transition.…”
Section: Resultssupporting
confidence: 57%
“…It is known that the chain length and concentration of the polymer can affect the process of LCST phase transition. For example, to observe a clear conformational transition in the case of computational studies of PNIPAAm, it was found that either the polymer chain length should be at least 30‐mer or the oligomer concentration should be high . In our single chain simulations, we observed a similar behavior for PMEO 2 MA that only 20‐ and 50‐mer polymers showed a LCST phase transition.…”
Section: Resultssupporting
confidence: 57%
“…Water content in the collapsed phase. To set up a system of collapsed PNIPAM polymers (20monomer-long atactic chains) above the LCST with the same chemical potential of water in as in bulk water, we first construct a system with two distinct phases [35,61]: a collapsed amorphous polymer phase in one part of the box, forming a membrane, and a polymer-free water reservoir in the other, as shown in Figure 1a. We use a novel, recently introduced, OPLS-based force field [62] for the PNI-PAM polymers, which better captures the thermoresponsiveness than the standard OPLS-AA [58].…”
Section: Resultsmentioning
confidence: 99%
“…For PNIPAM polymers we first tested the standard OPLS-AA [58] force field, which is among the most popular ones for PNIPAM simulations [27][28][29][30][31][32]35]. Since this force field did not yield satisfactory hydration results in the collapsed state (see Figure 1c) and also due to revealed issues with its thermo-responsive properties in the recent literature [61,96], we use its recent modification with recalculated partial charges by Palivec et al [62]. As has been demonstrated, the novel forcefield exhibits thermo-responsive properties of a single PNI-PAM polymer much closer to experimental observations.…”
Section: Atomistic Modelmentioning
confidence: 99%
“…The dissolution does not happen even for a slab of isotactic trimers in water (not shown), for both considered force fields, which is in agreement with simulations of trimers with several force fields. 22 The polymer regions at both sides of the central core (having half of the central density at the initial configuration) shrink along the run to produce larger densities (ρ s ) and thinner profiles (with width w). This shrinking process leads to the secondary maxima placed at the borders of the membrane, which are a consequence of the bending of the oligomer tips towards the central plane.…”
Section: B Membrane In Pure Watermentioning
confidence: 99%
“…A natural way of accounting for all these entangled effects together is by means of all-atom molecular simulations, with the price of strongly decreasing time scale and system size. This has been done mostly by considering an infinitely diluted oligomer chain in water for several force-fields 13,[19][20][21][22][23][24] and for different electrolyte solutions. 20 In particular, Tucker and Stevens have studied the T Θ dependence with the oligomer length for a syndiotactic chain, concluding that the large chain limit of T Θ is achieved with 30mers.…”
Section: Introductionmentioning
confidence: 99%